Antioxidant Properties and Storage Stability of Spray-dried Melastoma malabathricum L. Fruit Extract for Natural Colorant - Zahari, Nurul Syazwani; Sabran, Siti Fatimah; Mohd Asrah, Norhaidah; Abu Bakar, Mohd Fadzelly; Pa’ee, Furzani; Muhammad, Norhayati; Abu Bakar, Fazleen Izzany; Said, Mohd Khairil (Pertanika, 2025)
Melastoma malabathricum L. is a plant that is rich in anthocyanin, though its anthocyanin is low in stability. Therefore, this study aims to characterize the physicochemical properties of the encapsulated fruit extracts of M. malabathricum, to determine the antioxidant activities before and after encapsulation using 2,2-Diphenyl-1-picrylhydrazyl (DPPH), 2,2-Azino-bis-3- ethylbenzothiazoline-6-sulphonic acid (ABTS), and Ferric Reducing Antioxidant Power (FRAP) assays, expressed as IC50 values, and to assess the storage stability of the encapsulated fruit extract in different conditions based on the Total Anthocyanin Content (TAC) and Degradation Index (DI). The encapsulation was performed using a spray dryer and maltodextrin as the wall material. Crude extract with maltodextrin ratios of 1:1, 1:2 and 1:3 were tested, and TAC of the samples were determined using pH differential methods. The encapsulated extract was characterized according to their physical and chemical properties. Stability was evaluated under different conditions, including 20°C, 4°C and 25°C in the dark, and 25°C with light exposure for 90 days. Ratio 1:3 exhibited the lowest moisture content (5.77%) and solubility time (3s), while ratio 1:1 demonstrated the lowest bulk and tapped densities (0.366 g/ml and 0.5 g/ml). All ratios were acidic and displayed spherical particles with irregular surfaces. Ratio 1:1 showed the highest antioxidant activity with IC50 values of 28.50 μg/ml (DPPH), 49.03 μg/ ml (ABTS), and 39.97 μg/ml (FRAP). The most stable condition was at 4°C in the dark, while the ratio 1:2 was found to be the best ratio. Both factors can be considered to achieve stability for future applications.